When God stops fighting how religious violence ends - Juergensmeyer, Mark 1940- (University of California Press, 2022)
Preface -- The trajectory of imagined wars -- The apocalyptic war of the Islamic State -- The militant struggle of Mindanao Muslims -- The fight for Khalistan in India's Punjab -- How imagined wars end -- Interviews
Includes bibliographical references and index
Keywords: Moro Islamic Liberation Front; Islamischer Staat; Transformation; Beendigung; Religionssoziologie; Sikh; Religionskrieg; Irak; Philippinen; Punjab -- Indien; Violence / Religious aspects / Islam; Violence / Iraq / Religious aspects; Violence / Philippines / Religious aspects; Violence / India / Punjab / Religious aspects; Religious militants / Interviews; RELIGION / Religion, Politics & State; SOCIAL SCIENCE / Violence in Society